The impact of information ambiguity on the accuracy and precisionof analytical procedures in multi-location audits : An empirical study - Marwa Lotfy Fahmy Hamzawi; Mohammed Rashad Mehanna (Cairo : Marwa Lotfy Fahmy Hamzawi, 2014)
Analytical procedures are widely used by various auditors in various audit firms. It includes subjective decision making by the auditors. There are many risk factors affecting conducting auditing within multi-location companies. The current research tries to improve the decision making accuracy while conducting analytical procedures for multi-location companies, through the reduction of information ambiguity, by answering the following questions: In the account expectation stage, should the auditor depends on the prior year{u2019}s aggregated accounts? Or should the auditor depend on the disaggregated prior year{u2019}s accounts? If there is a considerable variance between the expected and the recorded accounts, should the auditors depend on the financial ratios analyses? In this case, should the auditor depend on the comparison of account balances that constitute these ratios rather than depending on the ratios as a complex version of data? At the other side
Thesis (M.Sc.) - Cairo University - Faculty of Commerce - Department of Accounting
Issued also as CD
Keywords: Analytical Procedures; Auditing; Multi-location companies